Yeast Srs2 helicase promotes redistribution of single-stranded DNA-Bound RPA and Rad52 in homologous recombination regulation - de Tullio, Luisina (2017)
Srs2 is a super-family 1 helicase that promotes genome stability by dismantling toxic DNA recombination intermediates. However, the mechanisms by which Srs2 remodels or resolves recombination intermediates remain poorly understood. Here, single-molecule imaging is used to visualize Srs2 in real time as it acts on single-stranded DNA (ssDNA) bound by protein factors that function in recombination. We demonstrate that Srs2 is highly processive and translocates rapidly (∼170 nt per second) in the 3′→5′ direction along ssDNA saturated with replication protein A (RPA). We show that RPA is evicted from DNA during the passage of Srs2. Remarkably, Srs2 also readily removes the recombination mediator Rad52 from RPA-ssDNA and, in doing so, promotes rapid redistribution of both Rad52 and RPA. These findings have important mechanistic implications for understanding how Srs2 and related nucleic acid motor proteins resolve potentially pathogenic nucleoprotein intermediates. De Tullio et al. develop a single-molecule assay for directly visualizing the behavior of the yeast helicase Srs2 as it acts upon single-stranded DNA (ssDNA). These experiments demonstrate that Srs2 is capable of rapid and processive translocation on ssDNA coated with the homologous recombination accessory proteins RPA and Rad52.